THE KEY MODES OF EXISTENTIALISM THROUGH THE PRISM OF VASYL STEFANYK'S NOVELS - Pankiv, M. Z. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
Aim. The article is devoted to the study of Vasyl Stefanyk's novels in the plane of the philosophy of existentialism. The aim is to show the main elements of this trend in the structure of the writer's artistic world. Subject: elements of the philosophy of existentialism and poetic ways of their personification in the art of Vasyl Stefanyk. The topicality of the research is to refute the thesis about the incompleteness of the Ukrainian literary process of creative searches. It is proving that elements of existentialism in Ukrainian literature existed in the end of the XIX - early XX centuries. Research methods. During studying of this topic we used the deductive approach as a general scientific method, so the texts for analysis selected those that are most suitable for consideration in the reception of existentialism. In particular, the comparative method, together with the analysis of categories, allowed us to analyze the stories of Vasyl Stefanyk through the prism of the key mods of this direction: loneliness, death, suffering, boundary situations, etc. Results. Using the method of analysis of categories and comparative studies, we considered the foundations of the philosophy of existentialism in literature, in particular in the stories of Vasyl Stefanyk, and determined the phenomenon of his work as the forerunner of this trend in Ukrainian literature. We believe that it was unjustly overtaken by critics, because the situations on the verge of life and death, inner harmony and despair, fateful choice are one of the most important features of the "literature of being," which, in turn, are elucidated by the author in the texts. The obtained materials and conclusions can find practical application at classes of Ukrainian literature during the study of Vasyl Stefanyk's works; at classes in the university to present a more voluminous picture of the figure of the writer, and may also need researchers of the philosophy of existentialism in literature.